2020
DOI: 10.1107/s2056989020001942
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a two-dimensional metal–organic framework assembled from lithium(I) and γ-cyclodextrin

Abstract: The crystal structure of the polymeric title compound, catena-poly[[[diaqualithium]-μ-γ-cyclodextrin(1−)-[aqualithium]-μ-γ-cyclodextrin(1−)] pentadecahydrate], {[Li2(C48H79O40)2(H2O)3]·15H2O} n , consists of deprotonated γ-cyclodextrin (CD) molecules assembled by lithium ions into metal–organic ribbons that are cross-linked by multiple O—H...O hydrogen bonds into sheets extending parallel to (0\overline11). Within a ribbon, one Li+ ion is coordinated by one deprotonated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In an effort to create a new electrode material for lithium-ion batteries, Krukle-Berzina et al [7] synthesized the first lithium-based CD-MOF three years later. The aforementioned Li-based CD-MOF consists of four oxygen atoms arranged in deformed tetrahedra to coordinate both Li + ions.…”
Section: Of 13mentioning
confidence: 99%
“…In an effort to create a new electrode material for lithium-ion batteries, Krukle-Berzina et al [7] synthesized the first lithium-based CD-MOF three years later. The aforementioned Li-based CD-MOF consists of four oxygen atoms arranged in deformed tetrahedra to coordinate both Li + ions.…”
Section: Of 13mentioning
confidence: 99%
“…Apart from the classic 3D structures described above, there are also reports on g-CD-MOFs exhibiting 2D structure or 2D layers stacked to form 3D structures. [104][105][106] For instance, one of these studies demonstrated the synthesis of a CD-MOF from polyoxometalate [P 10 Pd 15.5 O 50 ] 19À (POP) and g-CD. 104 It has an asymmetric unit cell that consists of two independent g-CDs and P 10 Pd 15.5 , of which the oxygen functions are mostly coordinated by K + ions.…”
Section: Cd-mofsmentioning
confidence: 99%
“…On an additional note, metal–organic ribbons (MORs) containing Li + ions and deprotonated CD molecules have also been reported. 106 These MORs exhibit a sheet-like structure due to crosslinking by hydrogen bonding.…”
Section: Synthesis Structure and Properties Of Cd-mof Materialsmentioning
confidence: 99%